2019
DOI: 10.5858/arpa.2019-0140-cp
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Staff Turnover: A College of American Pathologists Q-Probes Study of 23 Clinical Laboratories

Abstract: Context.— Knowledge of laboratory staff turnover rates are important to laboratory medical directors and hospital administrators who are responsible for ensuring adequate staffing of their clinical laboratories. The current turnover rates for laboratory employees are unknown. Objective.— To determine the 3-year average employee turnover rates for clinical laboratory staff and to survey the types of institutional human resource practices that may be associated with lower turnover rates. Design.— We collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…A 2014 review estimated that 53% of transfusion service/blood bank labs reported being understaffed (Chaffe et al ., ). High turnover of lab technical staff and lack of specialty‐trained/‐qualified technicians are becoming increasingly identified as major challenges to maintaining laboratory quality and minimising lab testing errors (Bolton‐Maggs et al ., ; Novis et al ., ). As fewer technical staff are being expected to perform increasing volumes of testing, any and all efforts to reduce unnecessary testing volume can be expected to have a positive impact on lab quality, as well as workplace/job satisfaction among technical staff.…”
Section: Discussionmentioning
confidence: 97%
“…A 2014 review estimated that 53% of transfusion service/blood bank labs reported being understaffed (Chaffe et al ., ). High turnover of lab technical staff and lack of specialty‐trained/‐qualified technicians are becoming increasingly identified as major challenges to maintaining laboratory quality and minimising lab testing errors (Bolton‐Maggs et al ., ; Novis et al ., ). As fewer technical staff are being expected to perform increasing volumes of testing, any and all efforts to reduce unnecessary testing volume can be expected to have a positive impact on lab quality, as well as workplace/job satisfaction among technical staff.…”
Section: Discussionmentioning
confidence: 97%
“…Novis et al . [ 19 ] studied staff turnover (departures per staff and per time) using a survey and found the median 3 year turnover was 14% in 14 US institutions. The 90 th percentile three-year turnover rate was 28%.…”
Section: Discussionmentioning
confidence: 99%
“…According to data obtained from one of these laboratory's Security and Exchange Commission's annual 10‐K filing, in 2018 it employed over 61000 employees and processed over 130 million patient‐specimens per year with its presence over 100 countries globally 5 . More importantly, according to a most recent pathology survey, Anatomic Pathology has the highest median 3‐year turnover rate out of the disciplines surveyed 6 . Therefore, understanding potential stressors that exist in large commercial cytology laboratories, and finding out the reasons why some cytotechnologists stay longer at a workplace than others, will be helpful for laboratories in understanding how they can address these issues to enhance work cultures, employee satisfaction, and laboratory quality.…”
Section: Introductionmentioning
confidence: 99%
“…According to the model's framework, stress and coping effort influence behaviour and outcomes 6 . When individuals are faced with a chronic stressor at work, they will first assess the situation to determine whether it is a negative or positive event (primary appraisal) and also what their options are, given the resources that are at their disposal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation